QUALITATIVE IDENTIFICATION OF BORAX CONTENT IN MEATBALL SNACKS USING TURMERIC PAPER AND SHALLOT EXTRACT - Cukri Rahma; Yusi Hidjrawan (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
Borax as a food additive chemical is very dangerous. Borax is prohibited from being used in food because it can cause various diseases such as cancer, kidney damage, and even death. This study aims to identify the borax content in the meatballs sold in Meulaboh City. The study design uses purposive sampling with a total of 20 meatball samples from each seller collected and continued by a qualitative test using turmeric paper and shallot extract. The study results show that all samples tested were free of borax. This can be seen from the absence of changes in turmeric paper and shallot extract. Therefore, it can be concluded that the meatballs sold in Meulaboh do not contain borax and are safe to consume.